The Influence of Indonesian Realistic Mathematics Approach to Improve Concept Understanding and Critical Thinking Skills of Fourth Grade Elementary School Students - Septia, Nur Septia Isma Gunarti; Fery Muhamad Firdaus; Budiawan (International Journal of Elementary Education, 2023)
Using real-world contexts in learning mathematics is necessary to hone students' minds. This study aims to analyze the use of the PMRI approach on students' conceptual understanding and critical thinking skills and the differences between students' conceptual understanding and critical thinking skills using the PMRI approach and students using conventional approaches. The type of research used is quasi-experimental, with a pretest-posttest control group design. The population used is fourth-grade elementary school students. The sampling technique used purposive cluster random sampling with a sample of 59 class IV students as the experimental class and 54 class students as the control class. Data were collected using multiple-choice test instruments and descriptions. Data analysis techniques used descriptive analysis test, normality test, homogeneity test, paired sample t-test and independent sample t-test. The results showed that first, using the PMRI approach affected students' conceptual understanding and critical thinking skills. The PMR approach could improve students' conceptual understanding and critical thinking skillss.